Taguatagua 1: New insights into the late Pleistocene fauna, paleoenvironment, and human subsistence in a unique lacustrine context in central Chile. (15th June 2020) - Labarca, Rafael; González-Guarda, Erwin; Lizama-Catalán, Álvaro; Villavicencio, Natalia A.; Alarcón-Muñoz, Jhonatan; Suazo-Lara, Felipe; Oyanadel-Urbina, Pablo; Soto-Huenchuman, Paula; Salazar, Christian; Soto-Acuña, Sergio; Buldrini, Karina E.
Abstract: The Laguna de Tagua Tagua has yielded two important late Pleistocene archaeological sites, Taguatagua 1 and Taguatagua 2, in which a clear early human exploitation of megafauna has been recorded. Particularly in Taguatagua 1 (TT-1), here re-dated around 12, 600 cal yr BP, an abundant small faunal assemblage was also recovered, which had not been previously studied in detail. Here we report the first comprehensive taxonomic and taphonomic analysis of this site. We identified 28 different taxa, including mollusks, fish, anurans, reptiles, birds, marsupials, rodents, carnivores, gomphotheres, horses and cervids, making this the richest late Pleistocene site in Chile so far. Among these, sixteen taxa are new for the Chilean late Pleistocene. Birds are the richest group, with ten taxa, followed by rodents with eight taxa. Most of the species currently inhabit the area, but we identified some locally extirpated taxa, together with extinct taxa (exclusively megamammals). Taphonomic analysis suggests a very complex depositional scenario, mostly related to lake-level oscillations which covered and exposed a mainly natural deposited small faunal assemblage. So far, we detected human-made modifications exclusively in horse and cervid bones. Current habitat requirements of the extant fauna, as well as dietary reconstruction of extinct fauna, suggest a highly variable climate and vegetation during the formation of TT-1 since taxa with preferences from semiarid to humid/wooded environments were identified. These results can be related to the changes from cold/wet to dry/warm conditions documented during the Pleistocene - Holocene transition. Highlights: TT-1 is the richest late Pleistocene fossil deposit in Chile, with 28 taxa identified. Fossil assemblage is composed mainly by small fauna. Clearly anthropic marks were detected on extinct horse and cervid bone. Ecological requirements of the taxa identified suggests humid and semiarid conditions.